2007
DOI: 10.1016/j.gene.2006.08.027
|View full text |Cite
|
Sign up to set email alerts
|

EP4 receptor regulates collagen type-I, MMP-1, and MMP-3 gene expression in human tendon fibroblasts in response to IL-1β treatment

Abstract: Tendinopathy is accompanied by inflammation, tendon matrix degradation, or both. Inflammatory cytokine IL-1beta, which is a potent inflammatory mediator, is likely present within the tendon. The purpose of this study was to determine the biological impact of IL-1beta on tendon fibroblasts by assessing the expression of cPLA(2), COX-2, PGE(2) and its receptors (EPs), collagen type-I, and MMPs. We also studied the role of the p38 MAPK pathway in IL-1beta-induced catabolic effects. We found that IL-1beta increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 58 publications
2
90
1
2
Order By: Relevance
“…The distribution rates and allele frequencies in our study are similar to those from previous reports from Japan (9,11,17,34,35 (9,10,33) (4,5,36,37 …”
Section: In This Study We Investigated the Relationship Of Gene Polysupporting
confidence: 91%
“…The distribution rates and allele frequencies in our study are similar to those from previous reports from Japan (9,11,17,34,35 (9,10,33) (4,5,36,37 …”
Section: In This Study We Investigated the Relationship Of Gene Polysupporting
confidence: 91%
“…An immense body of scientific work has shown that connective tissue MMP gene expression is regulated by various cytokines and signaling molecules (most importantly TGF-b, IL-1b, TNF-a, and Wnt) [160][161][162][163][164][165] but it is only vaguely understood how these signal transduction pathways are initiated and then coordinated toward a successful tissue repair [152]. Substantial scientific research effort is required to enable better understanding of how these aspects contribute to tissue repair outcome.…”
Section: The Fundamental Role Of Mechanical Forces In Regulating Tendmentioning
confidence: 99%
“…IL-1␤-induced up-regulation of COX-2 was ascribed to interaction of released PGE 2 with EP 4 receptors (Faour et al, 2001). IL-1␤ also increases PGE 2 production in human tendon fibroblasts, which mediates down-regulation of type 1 collagen via EP 4 receptors, which in turn may disturb tendon homeostasis (Thampatty et al, 2007).…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%